An example to illustrate several aspects of optimization theory in Managerial Economics - Lahiri, Somdeb (Managerial Economics, 2021)
We provide a single example that illustrates all aspects of linear, integer and dynamic programming, including such concepts such as value of perfect and imperfect information. Such problems, though extremely plausible and realistic are hardly ever discussed in managerial economics.